Implementasi Pelatihan dan Pengembangan Karyawan di Era Digital - Hasanah, Uswatun; Pasaribu, Ramadhan (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Digital transformation has brought fundamental changes in human resource management practices, especially in the aspect of employee training and development. This study aims to comprehensively examine how digital technology is integrated in HR training and development to improve work effectiveness and organizational competitiveness. This research uses a qualitative approach with a systematic literature study method of various scientific sources such as journals, books, research reports, and conference proceedings. The results show that digitization in training through e-learning, Learning Management System (LMS), and the use of Artificial Intelligence contribute significantly to improving employees’ technical competencies and soft skills. Digital training also enables flexible, personalized, and continuous learning. In addition, strategic HR development encourages an adaptive, collaborative, and innovative work culture amidst the challenges of Industry 4.0. Therefore, training and development integrated with digital technology is not only an efficiency solution, but also a long-term strategy in shaping a superior workforce that is ready to compete in the era of digital transformation.